2020
DOI: 10.5334/labphon.269
|View full text |Cite
|
Sign up to set email alerts
|

Nasal coda neutralization in Shanghai Mandarin: Articulatory and perceptual evidence

Abstract: Shanghai Mandarin is reported to neutralize /n/ and /ŋ/ after non-low vowels, a change also reported for other varieties of Chinese. However, the place of articulation of the resulting nasal is unclear. We used production and perception experiments to determine the contexts which condition neutralization and the place of articulation of the resulting nasal. Analysis of ultrasound data using a dimensionality reduction technique revealed that neutralization in production was dependent on the height of the preced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…The LD values were normalized to numbers between 0 and 1, with 0 set to be Baseline [k] and 1 to be Baseline [q]. By doing so, we can visualize the similarities of tongue contours using density plots (see Strycharczuk & Sebregts (2018) and Faytak et al (2020) for a similar approach).…”
Section: Discussionmentioning
confidence: 99%
“…The LD values were normalized to numbers between 0 and 1, with 0 set to be Baseline [k] and 1 to be Baseline [q]. By doing so, we can visualize the similarities of tongue contours using density plots (see Strycharczuk & Sebregts (2018) and Faytak et al (2020) for a similar approach).…”
Section: Discussionmentioning
confidence: 99%
“…The production and perception of nasalization have been investigated in many other branches of Mandarin and some southern dialects in China through acoustic analysis [3], nasometric measurements [4], perception studies [5], and ultrasound imaging [6]. Except for ultrasound imaging, all methods use indirect indicators and measurements (formants of nasal and oral vowel, the energy ratio of nasal to nasal plus oral, human behavioral experiment results, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Faytak et al (2020) measured the formant values at the vowel endpoint preceding a nasal coda in Standard Mandarin. They found that between /n/ and /ŋ/ codas, there is approximately a 300Hz difference in F2.…”
mentioning
confidence: 99%